2012
DOI: 10.1055/s-0032-1308977
|View full text |Cite
|
Sign up to set email alerts
|

Die Sichtweise der kommunalen Ebene über den Hausärztemangel – eine Befragung von Bürgermeistern in Baden-Württemberg

Abstract: The PS topic is of high relevance for communities in BW. In order to gain future physicians for their region, the majority of the communities are maintaining a high level of infrastructure and are willing to offer more actions. The young generation physicians need to be informed about these existing conditions. Innovative ideas should be implemented in individual communities as pilot projects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
13

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 3 publications
0
11
0
13
Order By: Relevance
“…From a previous study [11], we concluded that the majority of patients in Germany can reach a hospital within 30 minutes, therefore, we changed the original scale in relation to this measure. Also, the scale of the item “on-call duty” had to be changed, as in Germany the density of physicians is higher than in New Zealand [22] and moreover, not only GPs but all physicians working in ambulatory care have to take over on-call duties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a previous study [11], we concluded that the majority of patients in Germany can reach a hospital within 30 minutes, therefore, we changed the original scale in relation to this measure. Also, the scale of the item “on-call duty” had to be changed, as in Germany the density of physicians is higher than in New Zealand [22] and moreover, not only GPs but all physicians working in ambulatory care have to take over on-call duties.…”
Section: Discussionmentioning
confidence: 99%
“…In Germany, the GP shortage is a growing problem, especially in some “rural” areas [11,12]. Our research group decided to work on the understanding of “rurality” in Germany as it is a country with a history of minimal access to care inequalities…”
Section: Introductionmentioning
confidence: 99%
“…Zusätzlich zu den aus Altersgründen in den nächsten Jahren aus dem Beruf ausscheidenden Hausärzten werden durch die zu geringe Zahl an nachrückenden Fachärzten, der zunehmenden Tendenz zu größeren Praxen und dem Wunsch nach Teilzeittätigkeit zukünftig lokale Engpässe be fürchtet [17][18][19][20]. Daher wird insbesondere auf der kommunalen Ebene das Thema Hausärztemangel häufig diskutiert [21]. Vor diesem Hintergrund war es Ziel der vorliegenden Studie, die aktuelle Diskussion zur hausärztlichen Versorgungssituation um die Perspektive der Bürgermeister zu ergänzen.…”
Section: Discussionunclassified
“…Betrachtet man die Motive untereinander, dann schneiden diejenigen am schlechtesten ab, die für eine Niederlassung vom Gesundheitssystem gesteuert sind, wie beispielsweise "Notwendigkeit der Hausbesuche" oder "Notbzw. Bereitschaftsdienste [25][26][27][28].…”
Section: Itemunclassified